PENERAPAN SANKSI TERHADAP PELANGGARAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN OLEH PERSEROAN TERBATAS - Desy Fitri Zahra Birlani (2021)
The purpose of this study is to examine the reasons for a Limited Liability Company not carrying out Corporate Social Responsibility, and how to apply sanction to Limited Liability Companies that do not carry out Corporate Social Responsibility. This study uses a normative juridical research method, namely research sourced from library research with a statute approach. The result of the study shows that in implementing Corporate Social Responsibility there are still several obstacles for Limited Liability Companies such as limited funds, limited human resources and partnerships, as well as constraints regarding the relationship between the company and the community and government. As in the case of the Palu District Court decision No. 69/Pdt.G/2018/PN Pal, where several PTs that carry out the mining do not implement TJSL. Sanctions for companies that do not carry out Corporate Social Responsibility are regulated in Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 25 of 2007 concerning Investment, Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility, and also in several Regional Regulations. In the Palu City Regulation Number 13 of 2016 the sanctions are regulated in Article 4 paragraph (2). Regarding civil lawsuits based on Article 87 paragraph (1) of Law Number 32 of 2009 concerning Environmental Protection and Management based on elements of unlawful acts and can be subject to compensation sanctions.